2016
DOI: 10.1155/2016/4137908
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Rich Extract from Clinacanthus nutans Attenuates Hyperlipidemia‐Associated Oxidative Stress in Rats

Abstract: Clinacanthus nutans is used as traditional medicine in Asia but there are limited scientific studies to support its use. In this study, the stem and leaf of C. nutans were extracted using solvents of differing polarities, and their antioxidant capacities were determined using multiple antioxidant assays. The water and aqueous methanolic leaf extracts were further fractionated and their antioxidant capacities and phenolic compositions were tested. Furthermore, the efficacies of the water and aqueous methanolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 33 publications
(40 reference statements)
4
54
0
Order By: Relevance
“…The present study aims to investigate this plant by using doses of methanolic leaf extract of Clinacanthus nutans (MECN) similar to previous research [22,24]. Recent evidence has shown that methanolic leaf extract of Clinacanthus nutans improves lipid profiles in rats [17]. Polyphenols have been known to regulate lipid metabolism by inducing metabolic gene expression or trigger the transcription factors that play a significant part in metabolizing energy [25].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The present study aims to investigate this plant by using doses of methanolic leaf extract of Clinacanthus nutans (MECN) similar to previous research [22,24]. Recent evidence has shown that methanolic leaf extract of Clinacanthus nutans improves lipid profiles in rats [17]. Polyphenols have been known to regulate lipid metabolism by inducing metabolic gene expression or trigger the transcription factors that play a significant part in metabolizing energy [25].…”
Section: Introductionmentioning
confidence: 92%
“…It is intensively grown in tropical and subtropical Asian countries including Malaysia, Indonesia, Thailand, China and Vietnam [15]. Clinacanthus nutans contains important constituents such as phenolics, flavonoids, stigmasterol, β-sitosterol, lupeol, betulin, chlorophyll derivatives, protocatechuic acid, C-glycosyl flavones, vitexin, isovitexin, shaftoside, isomollupentin, 7-O-β-glucopyranoside, orientin, isoorientin, cerebrosides, steroids, triterpenoids, glycerides, monoacylmonogalactosylglycerol and sulfur-containing glucosides [16][17][18]. The phytochemical compounds, namely phenols, tannins, alkaloids, steroids, protocatechuic acid, and terpenes, may have the ability to exert hypolipidemic activity [19].…”
Section: Introductionmentioning
confidence: 99%
“…Lindau (Family: Acantheceae) commonly known as Sabah snake grass [28]. This plant is widely used for treating skin rashes, scorpion and insect bites, gastrointestinal complications, dysuria, menstrual function, anemia, jaundice, setting of fractured bones, diabetes mellitus, fever and diuretics [29]. Numerous bioactive have been demonstrated in C. nutans such as phenolics, flavonoids, sitosterol, stigmasterol, and chlorophyll derivatives [29].…”
Section: Introductionmentioning
confidence: 99%
“…This plant is widely used for treating skin rashes, scorpion and insect bites, gastrointestinal complications, dysuria, menstrual function, anemia, jaundice, setting of fractured bones, diabetes mellitus, fever and diuretics [29]. Numerous bioactive have been demonstrated in C. nutans such as phenolics, flavonoids, sitosterol, stigmasterol, and chlorophyll derivatives [29]. In addition, The C-glycosidic flavones such as shaftoside, isoorientin, orientin, isovitexin, and vitexin have been found to be the major flavonoids in the leaves of C. nutans [30,31], although protocatechnic acid was one of the most abundant [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation